IMPLEMENTASI PERLINDUNGAN BAGI ANAK KORBAN TINDAK PIDANA PROSTITUSI ONLINE OLEH DINAS PEMBERDAYAAN PEREMPUAN, PERLINDUNGAN ANAK, dan KEPENDUDUKAN PROVINSI JAWA TIMUR - Tiara, Dhea; Indawati, Yana (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Legal protection is a legal effort that must be provided by law enforcement officials to provide a sense of security, various threats from any party. The crime of prostitution is very widespread in society. This study aims to examine how legal protection is carried out by the East Java P3AK Service for child victims of online prostitution. This research is a juridical empirical type which collects data by observation, interviews and literature studies and is also analyzed using descriptive analysis methods. The data used are primary and secondary data. This research shows that there are two kinds of protection, namely preventive protection and repressive protection. The protection carried out by the East Java DP3AK Service for child victims of online prostitution is guided by Law Number 35 of 2014 concerning Child Protection